China's Approach to Disaster Risk Reduction: Human Security Challenges in a Time of Climate Change. (April 2017) - Renwick, Neil
Natural disasters strike at people's lives across the world but hit underdeveloped countries and societies' poorest hardest. Those living in the Asia-Pacific region are significantly more likely to experience natural disaster than those in any other part of the world. China is one of the most exposed to natural disasters, with a long history of devastating events and remains at high risk. China has undertaken major disaster risk reduction (DRR) reforms. Importantly, China is also increasingly committed to international cooperation over DRR within a Sendai Framework. Adopting a Human Security perspective, this article explains and critically evaluates China's DRR reforms. It highlights China's increased willingness to collaborate with international agencies over knowledge exchange and capacity building to improve its domestic DRR and contribute to the international DRR system. The study argues that China's reforms are a work in progress, but demonstrating improvement. It argues that China's expressed wish for closer international DRR cooperation is a new opportunity to mainstream China and it is incumbent on the international community and Chinese Government to build on emerging collaboration and grasp this long-overdue opportunity.